2022
DOI: 10.1038/s41537-022-00254-8
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic prescription, assumption and conversion to psychosis: resolving missing clinical links to optimize prevention through precision

Abstract: The current concept of clinical high-risk(CHR) of psychosis relies heavily on “below-threshold” (i.e. attenuated or limited and intermittent) psychotic positive phenomena as predictors of the risk for future progression to “above-threshold” positive symptoms (aka “transition” or “conversion”). Positive symptoms, even at attenuated levels are often treated with antipsychotics (AP) to achieve clinical stabilization and mitigate the psychopathological severity. The goal of this study is to contextually examine cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…In particular, this risk was not related to differences in pre‐test risk enrichment across the studies (Raballo et al, 2021b). In 2022, other investigations on single, longitudinal CHR‐P cohorts confirmed the negative prognostic value associated with baseline AP exposure (Preti et al, 2022; Zeng et al, 2022), which is probably due to different factors that are still unknown and under‐investigated (Zhang et al, 2022). In particular, baseline AP exposure in CHR‐P individuals may be considered as a functional equivalent of the psychometric transition to psychosis (Preti et al, 2022), as already postulated in the original ‘Ultra High‐Risk’ model (Yung et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…In particular, this risk was not related to differences in pre‐test risk enrichment across the studies (Raballo et al, 2021b). In 2022, other investigations on single, longitudinal CHR‐P cohorts confirmed the negative prognostic value associated with baseline AP exposure (Preti et al, 2022; Zeng et al, 2022), which is probably due to different factors that are still unknown and under‐investigated (Zhang et al, 2022). In particular, baseline AP exposure in CHR‐P individuals may be considered as a functional equivalent of the psychometric transition to psychosis (Preti et al, 2022), as already postulated in the original ‘Ultra High‐Risk’ model (Yung et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…It should be noted that in CHR-P individuals, baseline exposure to antipsychotics is associated with a greater risk of transition to psychosis both at a meta-analytical level (Raballo et al, 2020b; Raballo, Poletti, & Preti, 2023) and in subsequent field testing and reanalysis of available cohorts (Preti et al, 2022; Zhang et al, 2022), and it might be that BDZ – although this info is omitted in the source literature - could have been co-administered with antipsychotics, thereby capturing part of the AP-related pro-transition effect.…”
Section: Discussionmentioning
confidence: 99%
“…We also lacked details about the profile of symptoms at baseline by drug prescription, thus we were unable to determine whether BDZs were effectively prescribed to CHR-P help-seekers with more severe symptoms, e.g., with higher levels of anxiety or depression symptoms. There is some evidence that prescription of antipsychotics to help-seeking CHR-P is related to the severity of positive symptoms and greater impairment of global functioning (Zhang et al, 2022). Although we can surmise that the prescription of BDZ, especially when concomitant to the prescription of antipsychotics or antidepressants, might be related to greater severity at presentation, the lack of available information impedes a direct meta-analytical testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of psychosis is not only a change in behavioral appearance or brain function but also a characteristic change in the characteristics of immunoinflammatory markers in the early stage. The SHARP team 29,34,35 found that the imbalance of The results suggest that antipsychotic drugs should not be used prematurely in the at-risk population 27,28,40 as they are only valuable for <15% of the CHR population of a certain subtype [41][42][43] ; it is necessary to carry out individualized new intervention technologies for CHR subtypes of different biological dimensions. 3 Approximately 30% of the CHR population may recover naturally without intervention, and a large proportion of CHR are teenagers.…”
Section: Immune Dimension Of Inflammatory Cytokines and Complement Pr...mentioning
confidence: 99%